Bauran Promosi Olahraga Billiard di Instagram Studi Deskriptif pada Akun Instagram @bspoolcafe.bdg - Vivie Sulistiawaty; Anne Ratnasari (Bandung Conference Series: Communication Management, 2024)
Abstract. Instagram is the social media chosen as a bridge to conduct marketing communications. BS Pool & Café Instagram has 4,547 followers, contains some interesting photo content, videos, and feeds that have the aim of providing information about the world of billiards, as well as conducting market activities. BS Pool & Café Watukencana is a service company that rents out pool table space to play the sport of billiards in Bandung. Currently, the pool house is experiencing a crisis in the number of customers, the number of new pool houses in Bandung, and marketing communication strategies that are not yet qualified are obstacle in achieving the success of the BS Pool & Café Wastukencana pool house. From this phenomenon, the problems arose in this study, namely: (1) How is the presentation of billiards sports advertisements on Instagram? (2) How is the Billiard Sports Sales Promotion on Instagram? (3) How is the presentation of billiard sports fun games event information on Instagram? This research uses a quantitative methodology with a descriptive approach, the data collection technique used is the data of triangulations technique, where the way to obtain data in this study is by conducting interviews, observations, and literature studies. The data analysis technique in this study used descriptive data analysis techniques from B. Milles and Huberman, 2014. This analysis uses three streams of activities, namely data reduction, data presentation, and conclusion drawing. The result of this study are: The presentation of advertisements, sales promotions and the presentation of fun games event information on Instagram @bspoolcafe.bdg is very important for the success of marketing communication, how to choose the right media, how to communicate with customers, inform and offer a company’s product to its customers. Abstrak. Instagram merupakan media sosial yang dipilih sebagai jembatan penghubung untuk melakukan komunikasi pemasaran. Instagram BS Pool & Café memiliki jumlah followers sebanyak 4,547 followers, berisikan beberapa konten foto, video, serta feeds menarik yang mempunyai tujuan untuk memberikan informasi mengenai seputar dunia olahraga billiar, serta melakukan kegiatan pemasaran. BS Pool & Cafe Wastukencana adalah perusahaan pelayanan jasa yang menyewakan tempat meja billiard untuk bermain olahraga billiard di Kota Bandung. Saat ini rumah billiard sedang terjadi krisis penurunan jumlah customer, banyak nya rumah billiard yang baru di Kota Bandung, dan strategi komunikasi pemasaran yang belum mumpuni menjadi kendala dalam mencapai kesuksesan rumah billiard BS Pool & Café Wastukencana. Dari fenomena tersebut, maka muncul permasalahan dalam penelitian ini, yakni: (1) Bagaimana penyajian iklan olahraga billiard di Instagram? (2) Bagaimana Promosi Penjualan Olahraga Billiard di Instagram? (3) Bagiaman penyajian informai event fun games olahraga billiard di Instagram? Penelitian ini menggunakan metodologi kuantitatif dengan pendekatan deskriptif, Teknik pengumpulan data yang digunakan yaitu Teknik triangulasi data, dimana cara untuk memperoleh data pada penelitian ini dengan melakukan wawancara, observasi, dan studi pustaka. Teknik analisis data pada penelitian menggunakan Teknik analisis data deskriptif dari B. Milles dan Huberman, 2014. Analisis ini menggunakan tiga alur kegiatan, yaitu reduksi data, penyajian data, dan penarikan kesimpulan. Hasil dari penelitian ini adalah: adanya penyajian iklan, promosi penjualan dan penyajian informasi event fun games pada Instagram @bspoolcafe.bdg sangat berperan penting untuk keberhasilan komunikasi pemasaran, bagaimana cara memilih media yang tepat, cara berkomunikasi dengan customer, menginformasikan dan menawarkan suatu produk perusahaan kepada customer nya.